Non-photorealistic outdoor scene rendering : techniques and application - Liew Irene, Suet Fun; Sunar, Mohd. Shahrizal; Abdullah Bade, Abdullah Bade (IEEE, 2004)
Many researches in Non-Photorealistic Rendering (NPR) have been done to investigate a variety of techniques to simulate the styles of hand-drawn artists. Many applications in industrial, architectural, animated film production, technical design, and computer graphics designs have focused on rendering 3D models to depict non-photorealism. Most of them are based on rendering characters and object-based. This paper investigates on non-photorealistic rendering techniques for 3D outdoor scenes. Outdoor scene composed of a large extent of natural phenomena of landscapes, plants, trees, mountains, buildings, and many more. Techniques discussed in this paper include silhouette and cartoon-shaded renderings. Silhouette rendering implements Brute Force approach to determine the silhouette edges. Cel-shading algorithm in cartoon rendering renders the objects in the scene by manipulating directional or positional lightings with texture-shaded to give the scene cartoon look.